Notes towards the queer Asian city: Singapore and Hong Kong. (February 2017) - Yue, Audrey; Leung, Helen Hok-Sze
The last decade has witnessed the emergence and consolidation of new and established gay cities in East and Southeast Asia, in particular, the sexualisation of the Singapore city-state, the commerce-led boom of queer Bangkok, the rise of middle-class gay consumer cultures in Manila and Hong Kong, and the proliferation of underground LGBT scenes in Shanghai and Beijing. In the West, scholarships on urban gay centres such as San Francisco, New York and London focus on the paradigms of ethnicity (Sinfield, 1996), gentrification (Bell and Binnie, 2004) and creativity (Florida, 2002). Mapping the rise of commercial gay neighbourhoods by combining the history of ghettos and its post-closet geography of community villages, these studies chart a teleological model of sexual minority rights, group recognition and homonormative mainstream assimilation. Instead of defaulting to these specifically North American and European paradigms and debates, this paper attempts to formulate a different theoretical framework to understand the rise of the queer Asian city. Providing case studies on Singapore and Hong Kong, and deploying an inter-disciplinary approach including critical creative industrial studies and cultural studies this paper examines the intersections across the practices of gay clusters, urban renewal and social movement. It asks: if queer Asian sexual cultures are characterised by disjunctive modernities, how do such modernities shape their spatial geographies and produce the material specificities of each city?